2020
DOI: 10.31234/osf.io/prtyf
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Keeping Kids Busy: Family Factors Associated with Hands-on Play and Screen Time During the COVID-19 Pandemic

Abstract: Parent-child interactions are crucial for child development. The COVID-19 pandemic has negatively affected mental health and increased parenting challenges impacting parent-child functioning. The aim of the current study was to examine the relationship between parent factors and child activities to identify parental needs. A convenience sample of parents (N = 708), primarily mothers (n = 610; 87.4%) aged 35.59 years old (SD = 5.59; range = 21-72), with children ages 2-8 years completed an online questionnaire … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 66 publications
1
8
0
Order By: Relevance
“…Some of the studies discussed that feeling lonely and anxious motivated children and adolescents to use social media more often mainly to cope with the situation and with the lack of social contact; however, it resulted in even more negative feelings of anxiety, depression and loneliness ( 43 ). An aspect related to this that should be considered more generally is screen use ( 81 ). Excessive screen use is known to impact on sleep and physical activity ( 82 ) and has been linked with poorer language skills, lower school performance and classroom engagement, social/emotional difficulties, and reduced psychological well-being ( 81 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the studies discussed that feeling lonely and anxious motivated children and adolescents to use social media more often mainly to cope with the situation and with the lack of social contact; however, it resulted in even more negative feelings of anxiety, depression and loneliness ( 43 ). An aspect related to this that should be considered more generally is screen use ( 81 ). Excessive screen use is known to impact on sleep and physical activity ( 82 ) and has been linked with poorer language skills, lower school performance and classroom engagement, social/emotional difficulties, and reduced psychological well-being ( 81 ).…”
Section: Discussionmentioning
confidence: 99%
“…Excessive screen use is known to impact on sleep and physical activity ( 82 ) and has been linked with poorer language skills, lower school performance and classroom engagement, social/emotional difficulties, and reduced psychological well-being ( 81 ). Although screen media use among children and adolescents can be used with positive intentions, such as for education or to interact with friends and family and can award parents time to complete necessary tasks, it is an area of concern, especially during the COVID-19 pandemic ( 81 , 83 ). Research on online social network site (SNS) addiction, such as excessive and compulsive online social networking, is growing ( 84 ).…”
Section: Discussionmentioning
confidence: 99%
“…This review addressed an important factor in children's life during the ongoing COVID-19 pandemic, namely, children's play behaviors, providing valuable data regarding both children's indoor and outdoor activities. Various data from different regions of Europe and North America were retrieved, including 17 articles [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…Seventeen studies on the topic were identified. Among them, six studies were conducted in America (four in Canada [22][23][24][25], one in the USA [26], and one in Mexico [27]) and 11 were performed in Europe (five in Spain [28][29][30][31][32], two in Portugal [33,34], two in Ireland [35,36], one in the UK [37], and one in Poland [38]). Four of them had overlapping samples, but they have been included in Table 1 in the "overlapping studies" section" as they offered additional information regarding the issue examined in this paper.…”
Section: Selection Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation